Sino-Tibetan syntax - LaPolla, Randy J. (Oxford University Press, 2021)
This chapter discusses the word order patterns in the Sino-Tibetan languages. The two branches, Sinitic (Chinese) and Tibeto-Burman, differ in that clauses in Sinitic are largely verb-medial while those in Tibeto-Burman are verb-final. This chapter explains both patterns using information structure rather than grammatical relations, and looks at the historical factors that led to the different patterns in the two branches of the family. The evidence points to Proto-Sino-Tibetan having been verb-final, with the unmarked focus position being immediately preverbal. After the split of the two branches, the Sinitic side of the family developed verb-medial clauses due to a gradual shift to a clause-final focus position, possibly due at least in part to contact with Tai-Kadai languages, much as the Tibeto-Burman languages Bai and Karen have changed to verb-medial syntax due to contact with Sinitic in the case of Bai, and Tai and Mon-Khmer languages in the case of Karen.